2017
DOI: 10.24873/j.rpemd.2017.07.017
|View full text |Cite
|
Sign up to set email alerts
|

Design and validation of a short-implant rehabilitation model

Abstract: Objectives: This research intended to develop and validate a digital model that could be used to study the stresses and strains created in the different components involved in oral fixed rehabilitations with short implants. The validated model was then used to simulate a clinical-like situation.Methods: A digital model was created considering the posterior areas of the mandible. Its materialization obtained ten specimens of the experimental prototype. Seven of them were static compressive tested until failure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(2 citation statements)
references
References 31 publications
1
1
0
Order By: Relevance
“…Both tests intend to compare the mechanical behaviour of the numerical model with the experimental model. The former confirmed the sequence of failure of the models parts [67] and the last confirmed the displacement behaviour [68].…”
Section: Methodssupporting
confidence: 74%
“…Both tests intend to compare the mechanical behaviour of the numerical model with the experimental model. The former confirmed the sequence of failure of the models parts [67] and the last confirmed the displacement behaviour [68].…”
Section: Methodssupporting
confidence: 74%
“…For example, an FEA study on the influence of bone quality on stress distribution in IFCD showed that the less compact bones (poor bone quality) increased the stresses in implants and prosthetic superstructure and decreased the stresses in trabecular bone. 19 Ferreira et al 34 aimed to validate a numerical model that could be used to study stresses and strains created in the different components involved in oral fixed rehabilitations through FEA and static compressive load test (SCLT). Analyzing the tendencies of both models, an absolute match of their biomechanical behaviors can be observed, validating the computational model.…”
Section: Discussionmentioning
confidence: 99%